Effect of Late Pregnancy, Parturition and Early Lactation on T3, T4and Cortisol Level of Heifers and Cows - ojs_admin; Jassim ALkalby (مجلة علوم ذي قار, 2019)
The present study was carried out in the Al-Dujalah Cows Station which is located in Wasit governorate, Iraq. From 305 crossbred cows (Holstein x Friesian breeds), thirty six heifers (2.5-3.5) years old and thirty six multiparous cows (5-7) years old at different physiological conditions. The heifers and cows were divided into six equal groups depending on their physiological conditions as follows, group 1: Non-pregnant heifers (control), group 2: (Heifers in 7th month of pregnancy), group 3: (Heifers in 8th month of pregnancy), group 4: (Heifers in 9th month of pregnancy), group 5: (Heifers at 1-4 hours of parturition), group 6: (Heifers in first month of lactation). The multiparous cows were divided as that of heifers. The blood samples (5ml) were collected from Jugular vein at 2 weeks interval during pregnancy, at parturition (1-4 hours after parturition) and first month of lactation and deposited into plastic tube without anticoagulant to obtaining the serum samples for hormonal analysis. The study revealed the following results: A significant increase (p?0.05) in serum (T4) level was recorded in last month of pregnancy in both heifers and cows compared with control and other studied groups and a significant decrease in T3 level was observed in 7th month of pregnancy, at parturition and first month of lactation in cows while there was a significant increase in T3 level was recorded in 9th month of pregnancy in heifers compared with control and other studied groups. A significant increase (p?0.05) in serum cortisol level was recorded in first month lactating animals compared with control and other studied groups in both heifers and cows, and a significant increase in serum cortisol level was observed in control, 8th and 9th month of pregnancy and at parturition in cows compared with that of heifers.